Innocent until nominated : the breakdown of the presidential appointments process - MacKenzie, G. Calvin (Washington : Brookings Institution Press, 2011)
According to outspoken presidential scholar Cal Mackenzie, the presidential appointments process is a national disgrace. It encourages bullies and emboldens demagogues, silences the voices of responsibility, and nourishes the lowest forms of partisan combat. It uses innocent citizens as pawns in the petty games of politicians and stains the reputations of good people. It routinely violates fundamental democratic principles, undermines the quality and consistency of public management, and breaches simple decency. In short, at a time when the quality of political leadership in government matters.
Appointments past and future: how presidential appointees view the call to service -- "Political hacks" versus "bureaucrats": can't public servants get some respect? -- Contributors -- Index
Print version record.
JSTOR
Keywords: Cabinet officers -- Selection and appointment -- United States; Government executives -- Selection and appointment -- United States; Judges -- Selection and appointment -- United States; Presidents -- United States; United States -- Officials and employees -- Selection and appointment; Ministres -- Sélection et nomination -- États-Unis.; Hauts fonctionnaires -- Sélection et nomination -- États-Unis.; Présidents -- États-Unis.; POLITICAL SCIENCE -- Public Affairs & Administration; Cabinet officers -- Selection and appointment; Government executives -- Selection and appointment; Judges -- Selection and appointment; Presidents; United States